Does periodization work? Athletes perform better in major events than in minor - Matomäki, P.; Räntilä, A. (International Journal of Sports Science & Coaching, 2022)
Previous studies on periodization have led to the view that most athletes fail to peak at major events. These conclusions might be based on definitions of "peak performance" that are too narrow. In this study, a track and field athlete was defined as succeeding in a competition if their outcome was within the acceptable range from the best result of the season. The data are from seven championship finals and semifinals together with 42 Diamond League competitions from the 2010s, altogether 7,087 individual results. All field events and running events up to 400 m were included. The majority of athletes succeeded in major events (67.0% in sprint and 57.5% in field events). Overall, championship finals elicit success rates that are more than 70% higher than the basic level achieved in Diamond League competitions (p < 0.001). Success rates were systematically higher (over 60% higher) for the top three versus other competitors in every race (p < 0.001). When an acceptable range is adopted for the definition of what a successful result is, the majority of athletes manage to peak at the most important competitions. In addition, finishing in the top three in championship finals typically requires a peak performance.